ISOLATION OF ANTIMICROBIAL AGENTS THAT DISRUPTS THE FORMATION OF BIOFILM IN STAPHYLOCOCCUS AUREUS - Dr. Eswari Beeram, B. Vyshnavi, Sai Sreenivas, A. Sreevani, A. Harshitha, P. Govardhan, Dr. B. Sambasivaiah (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Biofilm formation is a multi-step process involves attachment of free floating bacteria to the solid matrix and secreting extracellular matrix substances finally succeeding in forming biofilm. Biofilm formation in bacteria helps in overhelming the environmental stressors, antibiotic resistance, offers enhanced protection against immunity and increased chances of genetic exchange. So, Phytochemical constituents that disrupt biofilm formation in microbes can help in designing new antibiotic agents. In this study we have selected five phytochemical constituents like Vigna mungo,Vigna unguiculata, Magniferous indica,Vigna radiata and Lathyrus sylvestris for the biofilm disruption. First we isolated S.aureus using nasal swab technique and confirmed the strain using Gram staining and catalase test. Futher to study the biofilm disruption we induced biofilm formation in S.aureus using solvents toulene and Glycerol. Biofilm confirmation was done by plating on EMB agar and Brain heart infusion agar. In the five phytochemical constituents Vigna mungo showed the positive response in disruption of toulene formed biofilm at concentrations 1.0% and 1.5%. Whereas Magnifera indica disrupted both toulene and glycerol formed biofilms at almost all concentrations (0.5%-2.5%) used.